Religion and organization theory - Tracey, Paul, 1974-; Phillips, Nelson; Lounsbury, Michael (Emerald, 2014)
Despite the profound influence that religious organizations exert, religion occupies a curiously marginal place in organization theory. This volume aims to make available in one place existing knowledge on religion and organizations, encouraging more organization theorists to include religion as part of their research activities and agenda.
Keywords: Organizational sociology.; Religion and sociology.; elektronické knihy; electronic books